Mental Health Response Community Training: Analysis of Viet Nam Cultural Values and Behaviors - Hien, Nguyen Thi Minh (Philippine Social Science Journal, 2025)
Despite Vietnam’s economic growth, the nation faces a critical shortage of mental health services, with only 143 clinicians available for the 14 million people suffering from disorders. Addressing this gap, this study evaluated the effectiveness of a pioneer two-day Mental Health First Aid (MHFA) training at Da Lat University. Analysis of pre- and post-training data from 55 participants demonstrated significant gains in clinical knowledge, assessment capabilities, and crisis intervention skills, particularly regarding depression and suicide. The enthusiasm for this first-of-its-kind initiative confirms the high value of expanding MHFA in Vietnam; however, future implementation requires ongoing evaluation to ensure the curriculum remains culturally responsive to local beliefs and norms that influence help-seeking behaviors.